Write the expressions for (s + r)(x) and (s - r)(x) and evaluate (sr)(3) .Suppose that the functions r and s are defined for all real numbers x as follows r(x) = x + 1 s(x) = 3x - 3

Write the expressions for s rx and s rx and evaluate sr3 Suppose that the functions r and s are defined for all real numbers x as follows rx x 1 sx 3x 3 class=

Respuesta :

ANSWER:

[tex]\begin{gathered} (s+r)(x)=4x-2 \\ (s-r)(x)=2x-4 \\ (s\cdot r)(3)=24 \end{gathered}[/tex]

STEP-BY-STEP EXPLANATION:

We have the following functions:

[tex]\begin{gathered} r\left(x\right)=x+1 \\ s\left(x\right)=3x-3 \end{gathered}[/tex]

We calculate each operation, just like this:

[tex]\begin{gathered} (s+r)(x)=3x-3+x+1=4x-2 \\ (s-r)(x)=3x-3-x-1=2x-4 \\ (s\cdot r)(3)=(3x-3)(x+1)=(3\cdot3-3)(3+1)=(9-3)(4)=(6)(4)=24 \end{gathered}[/tex]